PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN POTONGAN HARGA TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - B, Aqvila Fadini; Mustari, Mustari; Tadampali, Andi Caezar To; Nurjannah, Nurjannah (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The purpose of this study is to gain knowledge and understanding of the Influence of Brand Image, Product Quality, Discounts on Customer Satisfaction Through Purchasing Decisions as Intervening Variables on Shopee Users of Economics Department Students, FEB UNM. The method used is quantitative research technique with descriptive research type. The sample in the study was 100 Economics Department Students. Data analysis using the Partial Least Square Structural Equation Model (PLS-SEM) model. The results of the study obtained are Brand Image, Product Quality, Discounts on Purchasing Decisions. Brand Image, Product Quality, Discounts have a significant effect on Customer Satisfaction. Purchasing Decisions have a significant effect on Customer Satisfaction. Purchasing Decision can mediate Brand Image to Customer Satisfaction. Purchasing Decision can mediate Product Quality to Customer Satisfaction. Purchasing Decision can mediate Discount to Customer Satisfaction